Relationship between motor proficiency and blood pressure: the role of mediated by nutritional status - Pâmela Norraila da Silva; Jose Luiz Vieira; Francielle Ferreira da Rocha; Francielli Cheuczuk; Luciana Ferreira (Acta Scientiarum. Health Sciences, 2022)
Motor skills during childhood are extremely important for having an active lifestyle in adulthood; however, with the technological advance several plays and even the family environment have undergone changes, which affected the lifestyle adopted by the population. The present study aimed at investigating motor proficiency and blood pressure, as well as assessing the mediating role of nutritional status in such a correlation. This is a cross-sectional study carried out with 374 children aged 7 to 10 from the city of Maringá-PR. The nutritional status was measured by using the Body Mass Index (BMI) according to age and sex. The Bruininks-Oseretsky Test of Motor Proficiency, Second Edition, (BOT-2), was used to evaluate motor proficiency; the blood pressure was measured by using the Omron Deluxe HEM-7200® digital meter. The results showed a negative correlation between motor proficiency and body mass index and systolic and diastolic blood pressure. The analysis of structural equations revealed that there was no statistically significant direct impact of motor proficiency on blood pressure. However, when the mediation of nutritional status was included, a significant negative correlation between motor proficiency and nutritional status was seen, but positive in relation to systolic and diastolic blood pressure. In conclusion, motor proficiency has no direct influence on blood pressure; however, when mediated by nutritional status, the effect becomes significant. It is worth mentioning that the lower the motor proficiency and the higher the body mass, the higher the systolic and diastolic blood pressure was.